Soliton Solutions for Quasilinear Schrödinger Equations - Junheng Qu (Journal of Applied Mathematics)
By using a change of variables, we get new equations, whose respective associated functionals are well defined in and satisfy the geometric hypotheses of the mountain pass theorem. Using this fact, we obtain a nontrivial solution.